Pengaruh Gaya Penyampaian Konten Dakwah Ustadz Hanan Attaki di TikTok Terhadap Motivasi Diri Remaja - Saputri, Winda Agustina; Salsabila, Andini; Razzaq, Abdur; Nugraha, Muhamad Yudistira (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to examine the influence of Ustadz Hanan Attaki’s preaching style on TikTok on the self-motivation of teenagers in understanding and practicing Islamic teachings. A quantitative approach with a survey method was applied to 25 respondents who are TikTok-using teenagers and viewers of Ustadz Hanan Attaki’s da’wah content. Data were collected using a Likert-scale questionnaire. The results indicate that a relaxed, relatable, and communicative preaching style significantly influences teens’ religious motivation. A simple linear regression test showed a coefficient of determination (R²) of 0.856, indicating that 86% of the variation in self-motivation is explained by the preaching style. These findings highlight the importance of adapting preaching methods to the digital era, particularly through social media platforms.